An evaluation of the activities of the loyalty and partnership division of the Marketing department of Banglalink Digital Communications Limited - Khan, Shahed Abdullah (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.